PEG-OCL micelles for quercetin solubilization and inhibition of cancer cell growth - Khonkarn R. (2014)
In this study, quercetin (QCT), a flavonoid with high anticancer potential, was loaded into polymeric micelles of PEG-OCL (poly(ethylene glycol)-b-oligo(e-caprolactone)) with naphthyl or benzyl end groups in order to increase its aqueous solubility. The cytostatic activity of the QCT-loaded micelles toward different human cancer cell lines and normal cells was investigated. The results showed that the solubility of QCT entrapped in mPEG750-b-OCL micelles was substantially increased up to 1 mg/ml, which is approximately 110 times higher than that of its solubility in water (9 μg/ml). The average particle size of QCT-loaded micelles ranged from 14 to 19 nm. The QCT loading capacity of the polymeric micelles with naphthyl groups was higher than that with benzyl groups (10% and 6%, respectively). QCT-loaded, benzyland naphthyl-modified micelles effectively inhibited the growth of both sensitive and resistance cancer cells (human erythromyelogenous leukemia cells (K562) and small lung carcinoma cells (GLC4)). However, the benzyl-modified micelles have a good cytocompatibility (in the concentration range investigated (up to 100 μg/ml), they are well tolerated by living cells), whereas their naphthyl counterparts showed some cytotoxicity at higher concentrations (60-100 μg/ml). Flow cytometry demonstrated that the mechanism underlying the growth inhibitory effect of QCT in its free form was inducing cell cycle arrest at the G2/M phase. Benzyl-modified micelles loaded with QCT also exhibited this cycle arresting the effect of cancer cells. In conclusion, this paper shows the enhancement of solubility and cell cycle arrest of QCT loaded into micelles composed of mPEG750-b-OCL modified with benzyl end groups. These micelles are therefore considered to be an attractive vehicle for the (targeted) delivery of QCT to tumors. © 2011 Elsevier B.V.